Supplemental Bacillus subtilis PB6 Improves Growth Performance and Gut Health in Broilers Challenged with Clostridium perfringens - Yan Liu (Hindawi Limited, 2021)
Clostridium perfringens (CP) is the principal pathogenic bacterium of chicken necrotic enteritis (NE), which causes substantial economic losses in poultry worldwide. Although probiotics are known to provide multiple benefits, little is known about the potential effects of Bacillus subtilis (B. subtilis) application in preventing CP-induced necrotic enteritis. In this study, 450 male Arbor Acres broilers were divided into 5 experimental treatments: A: basal diet (control group); B: basal diet and CP challenge (model group); C: CP challenge+10 mg/kg enramycin (positive control group); D: CP challenge+4×107 CFU/kg of feed B. subtilis PB6 (PB6 low-dosage group); and E: CP challenge+6×107 CFU/kg of feed B. subtilis PB6 (PB6 high-dosage group). There were 6 replicate pens per treatment with 15 broilers per pen. The present research examined the effect of Bacillus subtilis PB6 (B. subtilis PB6) on growth performance, mRNA expression of intestinal cytokines and tight junctions, and gut flora composition in broilers challenged with CP. The entire experiment was divided into two phases: the non-CP challenge phase (d0–18) and the CP challenge phase (d18–26). PB6 did not increase the growth performance during the first stage, but the PB6 high-dosage group was found to have larger body weight gain and ADFI during the CP challenge stage. Feed supplementation with PB6 reduced the lesion score of challenged chicks, with increased tight junction-related gene expression (occludin and ZO-1) and decreased TNF-α expression compared with CP-infected birds. A decrease in the abundance of Clostridium XI, Streptococcus, and Staphylococcus was observed after CP infection (P<0.05), while supplementation with PB6 restored the ileal microbial composition. In conclusion, administration of B. subtilis PB6 improved growth performance, enhanced intestinal barrier function, and mitigated intestinal inflammation/lesions, which might be due to its restoring effects on the ileal microbial composition in CP-challenged broilers.